Long-term outcomes after chest wall resection and repair with titanium bars and sternal plates - Clermidy, Hugo; Fadel, Guillaume; De Lemos, Alexandra; Pradere, Pauline; Mitilian, Delphine; Girault, Antoine; Menager, Jean-Baptiste; Fabre, Dominique; Mussot, Sacha; Leymarie, Nicolas; Fadel, Elie; Mercier, Olaf (Frontiers in Surgery, 2022)
Objectives: En-bloc complete resection remains the treatment of choice of localized chest wall (CW) tumors. Titanium bars reconstruction demonstrated encouraging results with satisfactory early outcomes. However, long-term outcomes remain under reported. The purpose of this study was to evaluate long-term outcomes after CW resection and repair with titanium devices. Methods: From June 2012 to December 2018, we retrospectively reviewed all patients with CW tumors who underwent surgical resection and repair using titanium. Long-term outcomes were assessed. Results: We identified 87 patients who underwent CW tumor resections and titanium reconstruction. 68 patients were included in the study (excluding benign tumors, Pancoast tumors, palliative surgeries or clavicle reconstruction). There were 29 sarcomas, 20 isolated chest wall metastasis, 8 lung cancers, 4 breast cancers, 3 thymic malignancies, 2 sarcomatoid mesothelioma and 1 desmoid tumor. Complete resection was achieved in 64 patients (94%), R1 resection in 4 patients (6%). Resection involved 1 rib in 2 patients, 2 ribs in 13, 3 ribs in 18, 4 ribs in 9, 5 ribs in 2, 7 ribs in 1, partial sternum in 15 and full sternum in 16 patients. No patient experienced flail chest. The 1- 3- and 5-year overall survival rate and disease-free survival were 82.3%/61.4%/57.3% and 67.6%/57.3%/52.6%, respectively. Surgical site infection occurred in 18% (n=12). 11/12 patients had an early infection (<1 year) which required material removal in 6 patients. Asymptomatic connector unsealing occurred in 6% (n=4) with only one reintervention. Titanium allergy has never been reported. Chronic chest pain (more than 3 months after surgery, with daily use of pain killer) was reported in 24% of patients. Conclusion: CW resections with titanium reconstruction are associated with long-term survivors. Titanium devices were safe, reliable and achieved satisfactory oncological results with low morbidity and implant related complication rates.